تعالق الشخصية مع ذات السارد في الخطاب الروائي رواية العشق والموت في الزمن الحرّاشي للطاهر وطار أنموذجا - عـلاّ, عبـد الرزاق (University of Eloued جامعة الوادي, 2016)
من الروايات التي تداخلت فيها الأدوار وتآلفت فيها الشخصية الروائية مع ذات السارد ،وجدنا رواية " الموت والعشق في الزمن الحراشي "للطاهر وطار ،والتي عدّها العديد من الدّارسين صورة مصغرة لحياة الكاتب و مساره النضالي ، فقد عكست الشخصية الرئيسية - جميلة- شخصية الكاتب الذي جعلها تتكلم بلسان حاله ، معبرة عن مواقفه وآرائه السّياسية والأيديولوجية تجاه الواقع .وهو ما سنحاول الكشف عنه في هذا المقال. The novel of Tahir Wattar " Adoration and death in the time of AL-Harachi” Al ouch wa al mawt fi al zaman al Harachi ) is one of the important novels which were distinguished by the interference of roles, and the interaction between the character and the narrator. Many scholars considered it as a thumbnail image of the writer’s life and his path of struggle. The main character “Djamila” reflected the personality of the writer and reflected his positions, in addition to his ideological and political opinions towards the reality. These issues will be discussed in this article.
Keywords: الموت والعشق في الزمن الحراشي، الطاهر وطار، جميلة; Adoration and death in the time of AL-Harachi, Tahir Wattar, Djamila